The relationship between workplace support and job satisfaction amongst teachers at three different secondary school in Taman Maluri / Raja Norashikin Raja Razak - Raja Razak, Raja Norashikin (Faculty of Office Management and Technology, 2016)
The purpose of this study is to find out the relationship between job satisfaction and workplace support amongst teachers. 150 survey questionnaires were completed by secondary school teachers from three different secondary schools in Taman Maluri area. Questionnaire was used as an instrument to collect the data. The researches determine the dimension that exist in workplace support and it implication toward the job satisfaction. The workplace support consists of four elements which is perceived organization support, supervisor support, co-workers support and mentoring Based on the finding, it shows that every variables has association with job satisfaction. Supervisor support had that the strong association with job satisfaction which is (r=0.802,p=0.000) and the coworker support had a moderate association which is (r=0.428,p=0.000) compared to others variable. Schools that provide more on workplace support towards teachers will lead to higher on the job satisfaction. Hence, it also will increase teachers productivity in doing their work. Beside that, researcher only focus on secondary schools at Taman Maluri area. Meanwhile primary schools are excluded. It can be recommended that the researcher study can be done in a larger scale and future studies can cover other schools instead of these three school. Future researcher also can cover on type of school in these studies in order to get are reliable findings.